ADDITION OF PUMPKIN PEEL FLOUR AFFECT PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF BOVINE BURGER - Hartmann, Giovanna Luiza; Marconato, Allana Mariny; Romeiro Santos, Mirelly Marques; do Amaral, Luane Aparecida; dos Santos, Elisvânia Freitas; Novello, Daiana (International Journal of Research -GRANTHAALAYAH, 2020)
The current study aimed to evaluate the influence of the addition of pumpkin peel flour (PPF) on physicochemical, cooking and sensory characteristics of bovine burger. Five hamburgers were formulated: F1 - standard (0% PPF) and the others added 1% (F2), 2% (F3), 3% (F4) and 4% (F5) of PPF. The PPF was characterized by high contents of minerals, carbohydrate and dietary fiber, which improved nutritional profile of hamburger. There was an increase on cooking yield, moisture retention and reduction of shrinkage and fat retention, as the level of PPF addition increased. The incorporation of PPF at 3% and 4% in the product increased significantly (p<0.05) the values of L*, a* and b*. Similar acceptability to the standard sample was verified on products with addition of up to 3% PPF. All formulations showed an acceptability index greater than 70%. Thus PPF is a potential ingredient for the formulation of bovine burger to improve its nutritional and technological properties without modification of the sensorial characteristics.